Editorial for Special Issue “U-Pb Dating and Chemistry of Zircon in Metamorphic, Magmatic and Sedimentary Rocks” - Annamaria Fornelli (MDPI AG, 2021)
This Special Issue was conceived with the aim of contributing to disclosure of the applications of U-Pb dating and zircon chemistry for deciphering the growth and the evolution of the continental crust [...]